2020
DOI: 10.1159/000511938
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Stroke Glycemic Variability Estimated by Glycated Albumin Is Associated with Early Neurological Deterioration and Poor Functional Outcome in Prediabetic Patients with Acute Ischemic Stroke

Abstract: <b><i>Introduction:</i></b> Whether glycemic variability prior to stroke increases the risk of stroke outcomes in prediabetic patients presenting with acute ischemic stroke is still unclear. We evaluated whether pre-stroke glycemic variability, estimated by glycated albumin (GA), increased early neurological deterioration (END) and functional outcomes in prediabetic patients with acute ischemic stroke. <b><i>Methods:</i></b> A total of 215 acute ischemic stroke p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
(38 reference statements)
1
13
1
1
Order By: Relevance
“…However, the association between HbA1c and functional outcomes remains controversial 21 , 22 . In contrast, previous clinical studies on prestroke glycemic variability showed consistent results, and glycemic variability was associated with poor outcomes in stroke patients 11 , 23 . Similar to previous studies, we showed that a high GA level increased the risk of poor functional outcomes in patients treated with IVT.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…However, the association between HbA1c and functional outcomes remains controversial 21 , 22 . In contrast, previous clinical studies on prestroke glycemic variability showed consistent results, and glycemic variability was associated with poor outcomes in stroke patients 11 , 23 . Similar to previous studies, we showed that a high GA level increased the risk of poor functional outcomes in patients treated with IVT.…”
Section: Discussioncontrasting
confidence: 58%
“…Recent previous studies established that a GA level ≥ 16.0% reflected the presence of prestroke glycemic variability based on the following equation of HbA1c and GA: HbA1c = 0.216 × GA + 2.978 11 , 23 , 31 . According to this equation, we divided the subjects into two groups: a higher GA group (GA ≥ 16.0%) and a lower GA group (GA < 16.0%).…”
Section: Methodsmentioning
confidence: 99%
“…Also, GA has shown different impact on stroke outcomes being associated with only large artery atherosclerosis but not with small vessel occlusion and cardioembolism in diabetic individuals with acute ischemic stroke [ 30 ]. However, other study reported association of GA with early neurological deterioration in prediabetic individuals with acute ischemic stroke [ 31 ]. Reflecting short-term glycemia, FA and GA levels can be affected by acute blood glucose change, albumin turnover or metabolism [ 32 ] and therefore reflects its variability in a disease specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying factors associated with severe intracranial artery stenosis is important because patients with severe intracranial stenosis have the highest rate of recurrent stroke [ 2 , 3 ]. Furthermore, glucose fluctuation is also associated with early neurological deterioration and poor functional outcome in patients with acute ischemic stroke [ 45 ]. Interventions for glucose fluctuation can prevent intracranial artery stenosis and ischemic stroke in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%